Validation Of Endogenous Reference Genes For Relative Quantitation Studies Of Gene Expression In Nasopharyngeal Carcinoma - Ashley Edward Roy, Soosay; Ismail Maamar, Makhzoum Alhwij; Parvathee, Ponniah; Khoo, Alan Soo Beng; Wong, Chun Yi (Malaysian Society of Applied Biology, 2018)
Reverse transcription real-time quantitative polymerase chain reaction (RT-qPCR) is a useful molecular contraption in translational biomedical research and clinical settings. RT-qPCR requires normalization. Housekeeping gene (HKG) as reference gene (RG) is commonly used for the relative quantification of the target gene (TG) in gene profiling assays. Normalization requires stably expressed endogenous RG. Recently, RGs were found to be regulated in a various experimental milieu in different tissues. Therefore, it is pertinent to identify HKGs that are stably expressed and are independent of factors influencing the cell. To validate 4 endogenous RGs for the relative quantification of TGs in gene expression analysis performed via RTqPCR in nasopharyngeal carcinoma. The qbase+ software utilizing geNorm analysis identified GAPDH, TBP and YARS as stably expressed HKGs. ACTB was the least stable RG in this study. The most suitable set of RG for NPC gene expression studies include GAPDH, TBP and YARS. No single gene was identified as the best RG for expression study. The RG that can be utilized during RT-qPCR on normal and malignant nasopharyngeal tissue samples is a collection of 3 genes (GAPDH, TBP and YARS) used as an average.